Role of IGFBP7 in Diabetic Nephropathy: TGF-β1 Induces IGFBP7 via Smad2/4 in Human Renal Proximal Tubular Epithelial Cells. - Jun Watanabe; Yumi Takiyama; Jun Honjyo; Yuichi Makino; Yukihiro Fujita; Masatoshi Tateno; Masakazu Haneda (PLoS ONE)
Tubular injury is one of the important determinants of progressive renal failure in diabetic nephropathy (DN), and TGF-β1 has been implicated in the pathogenesis of tubulointerstitial disease that characterizes proteinuric renal disease. The aim of this study was to identify novel therapeutic target molecules that play a role in the tubule damage of DN. We used an LC-MS/MS-based proteomic technique and human renal proximal epithelial cells (HRPTECs). Urine samples from Japanese patients with type 2 diabetes (n = 46) were used to quantify the candidate protein. Several proteins in HRPTECs in cultured media were observed to be driven by TGF-β1, one of which was 33-kDa IGFBP7, which is a member of IGFBP family. TGF-β1 up-regulated the expressions of IGFBP7 mRNA and protein in a dose- and time-dependent fashion via Smad2 and 4, but not MAPK pathways in HRPTECs. In addition, the knockdown of IGFBP7 restored the TGF-β1-induced epithelial to mesenchymal transition (EMT). In the immunohistochemical analysis, IGFBP7 was localized to the cytoplasm of tubular cells but not that of glomerular cells in diabetic kidney. Urinary IGFBP7 levels were significantly higher in the patients with macroalbuminuria and were correlated with age (r = 0.308, p = 0.037), eGFR (r = -0.376, p = 0.01), urinary β2-microglobulin (r = 0.385, p = 0.008), and urinary N-acetyl-beta-D-glucosaminidase (NAG) (r = 0.502, p = 0.000). A multivariate regression analysis identified urinary NAG and age as determinants associated with urinary IGFBP7 levels. In conclusion, our data suggest that TGF-β1 enhances IGFBP7 via Smad2/4 pathways, and that IGFBP7 might be involved in the TGF-β1-induced tubular injury in DN.